Tool wear during milling laminated carbon fibre reinforced plastic - Muhamad Khairussaleh, Nor Khairusshima; A.K.M, Amin; C.H., Che Hassan; A.G. , Jaharah (Trans Tech Publications Ltd., Switzerland, 2015)

(untitled)
Carbon fibre reinforced plastic (CFRP) is a composite which has the best strength to weight ratio among the construction materials. It becomes valuable as the demand for this composite has increased dramatically especially in automobile and aerospace industry. Cutting speed of 160–194 m/min and a feed rate of 0.14–0.225 mm/tooth on solid uncoated carbide during the milling process were discussed. It is observed that the wear area is found polished and shining which is due to the abrasive nature of the carbon. The wear region is found high at higher cutting speeds and feed rates. The reduction of tool life is 40%, 30% and 14% as the cutting speed, feed rate increase and depth of cut increased respectively.